2023
DOI: 10.21037/tp-22-358
|View full text |Cite
|
Sign up to set email alerts
|

The actual duration of preoperative fasting in pediatric patients, and its effects on hunger and thirst: a prospective observational study

Abstract: Background: Preoperative fasting time for food and clear liquid was recommended as 2 and 6 h to prevent pulmonary aspiration. Prolonged fasting led to ketosis, hypotension, and patient discomfort. This study aimed to investigate the actual duration of preoperative fasting in pediatric patients, its effects on hunger and thirst, and factors that influence hunger and thirst.Methods: This prospective observational study recruited participants aged 0-15 years who were scheduled for elective surgery or for other pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
3
0
2
Order By: Relevance
“…Moreover, the significant association between adverse events and longer fasting times should encourage anesthesiologists, and in general all the perioperative health care personnel, to strictly adhere to the recommended guidelines to avoid excessive fasting times. Hypovolemia and/or dehydration in pediatric patients might lead to clinically significant adverse events [ 4 6 ]. Even if clinical consequences of dehydration were only partially and generically verified by our observations, and therefore likely underestimated, our study confirmed the findings reported by other studies [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the significant association between adverse events and longer fasting times should encourage anesthesiologists, and in general all the perioperative health care personnel, to strictly adhere to the recommended guidelines to avoid excessive fasting times. Hypovolemia and/or dehydration in pediatric patients might lead to clinically significant adverse events [ 4 6 ]. Even if clinical consequences of dehydration were only partially and generically verified by our observations, and therefore likely underestimated, our study confirmed the findings reported by other studies [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients were considered compliant with the preoperative fasting protocol if clear fluids fasting time was between 60 and 119 min. The upper limit of this time range was chosen considering the old ESA preoperative fasting guidelines [ 9 ] recommending clear fluids until 2 h before the induction of anesthesia and being aware that preoperative clear fluids fasting times remain significantly longer than 120 min worldwide [ 4 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…В то же время в клинической практике продолжительность предоперационного голодания существенно превышает рекомендованное время. N. Aroonpruksakul et al (2023) продемонстрировали, что продолжительность отказа от твердой пищи и прозрачной жидкости составили 11,1 и 10,0 часов соответственно [5].…”
Section: Introductionunclassified
“…Оно будет лишь усугублять ситуацию развитием гипогликемии, обезвоживанием, развитием выраженного биохимического дисбаланса [12][13][14][15]. В этой связи важно, чтобы анестезиологи знали о данных обстоятельствах и были подготовлены для адекватной предоперационной подготовки и эффективного ведения таких пациентов.…”
unclassified